Nucleocapsid protein enhances spike- and RBD-specific humoral and cellular immune responses in protein-based SARS-CoV-2 vaccine - Gröhn, Stina; Lehto, Heini; Soppela, Saana; Naves, Rauno A.; Ritvos, Mikael A.; Iakubovskaia, Alina; Lampinen, Vili; Mustonen, Iiris; Pakkala, Sanniina; Husu, Elizaveta; Kakkola, Laura; Julkunen, Ilkka; et al. (Springer Science and Business Media LLC, 2026)
Background
Current COVID-19 vaccines are effective at preventing severe disease but provide limited protection against infection and transmission, particularly as new variants emerge. Vaccines capable of inducing both systemic and mucosal immunity and robust T cell responses, may offer broader and more long-lasting protection. This study aimed to evaluate protein-based vaccine candidates incorporating SARS-CoV-2 spike (S) and its receptor-binding domain (RBD), as well as nucleocapsid protein (N) antigens administered through different immunization schemes.
Methods
Mice were immunized three times at four-week intervals with vaccine formulations containing Fc-fused RBD proteins, S, and/or N proteins. Vaccines were administered intranasally, subcutaneously, or with subcutaneous or intramuscular priming followed by intranasal boosting. Branched polyethylenimine (BPEI) was used as a mucosal adjuvant, and Adjuvant system 04 (AS04) for intramuscular administration. Depending on the experiment, BPEI or AS04 was used for subcutaneous immunizations. Systemic antibody responses were assessed from serum samples and mucosal antibody responses from bronchoalveolar lavage samples by ELISA. Cellular responses were measured from splenocytes after antigen stimulation by FluoroSpot analysis of cytokine secretion.
Results
Fc-fused RBD antigens elicited higher antibody responses than whole S protein. Inclusion of low amount of N protein enhanced RBD- and S-specific systemic and mucosal IgG and IgA responses, and significantly increased splenocyte IL-2 and IFN-γ secretion. Intranasal vaccination alone induced variable mucosal antibody responses, whereas intramuscular priming followed by intranasal boosting consistently produced higher systemic IgG levels, robust mucosal responses, and T cell activity. Neutralizing antibodies were negligible in intranasally primed groups but were detectable in most animals receiving intramuscular priming. Among all regimens, the combination of intramuscular priming with N-containing formulations generated the highest magnitude and breadth of humoral and cellular responses. All vaccine formulations were well tolerated with no adverse effects observed.
Conclusions
Protein-based vaccines incorporating N together with Fc-fused RBD antigens significantly broaden and enhance immune responses in mice. Intramuscular priming followed by intranasal boosting proved superior to other regimens, inducing strong systemic, mucosal, and cellular immunity. These findings suggest that inclusion of conserved internal virus antigens and heterologous prime-boost strategies may improve durability and breadth of protection, supporting their development as next-generation COVID-19 vaccines.